2021
DOI: 10.3390/electronics10212562
|View full text |Cite
|
Sign up to set email alerts
|

An Anomaly-Based Intrusion Detection System for Internet of Medical Things Networks

Abstract: Over the past few years, the healthcare sector is being transformed due to the rise of the Internet of Things (IoT) and the introduction of the Internet of Medical Things (IoMT) technology, whose purpose is the improvement of the patient’s quality of life. Nevertheless, the heterogenous and resource-constrained characteristics of IoMT networks make them vulnerable to a wide range of threats. Thus, novel security mechanisms, such as accurate and efficient anomaly-based intrusion detection systems (AIDSs), consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…Despite the numerous defense mechanisms in place, the authors of [25,26] have found that bandwidth availability and computer resource security remain problematic. Due to a surge in valid traffic and its resemblance to attack traffic, the DDoS problem became more urgent.…”
Section: Related Workmentioning
confidence: 99%
“…Despite the numerous defense mechanisms in place, the authors of [25,26] have found that bandwidth availability and computer resource security remain problematic. Due to a surge in valid traffic and its resemblance to attack traffic, the DDoS problem became more urgent.…”
Section: Related Workmentioning
confidence: 99%
“…Jamming attacks can disrupt communication between medical sensors in a WBAN system. This study proposed a novel intrusion detection system (IDS) based on network measurements [ 39 ] to distinguish between false alarms caused by jamming conditions and normal state. Our suggested method identifies three types of jamming to lessen false positives and increase detection rates.…”
Section: Related Workmentioning
confidence: 99%
“…Because of their unique characteristics, IoMT networks require novel security approaches, such as highly accurate and efficient anomaly-based intrusion detection systems (AIDSs), to reach their full commercial potential. Anomaly-based intrusion detection (AIDS) was proposed by [ 39 ] as a viable security measure for IoMT networks. It is planned to use a combination of host- and network-based technologies to collect logs from IoMT devices and gateways, as well as data from the edge of the network.…”
Section: Related Workmentioning
confidence: 99%
“…The environment of the Internet of things provides easy and simple access to the data environment and provides ease of handling by doctors. Zachos et al [ 26 ] proposed a system based on the Internet of things to detect AIDS. This was achieved by collecting data using the Internet of things system dedicated to detecting AIDS and measuring minute deviations in that data.…”
Section: Introductionmentioning
confidence: 99%